Agricultural input modifies trophic niche and basal energy source of a top predator across human-modified landscapes - Pereira, André C.; Mancuso, Christy J.; Newsome, Seth D.; Nardoto, Gabriela B.; Colli, Guarino R. (Frontiers in Ecology and Evolution, 2023)
Land-use conversion and resulting habitat fragmentation can affect the source(s) of primary productivity that fuels food webs and alter their structure in ways that leads to biodiversity loss. We investigated the effects of landscape modification on food webs in the Araguaia River floodplain in central Brazil using the top predator, and indicator species Caiman crocodilus (Crocodilia, Alligatoridae). We measured carbon (δ13C) and nitrogen (δ15N) isotope values of three tissues with different isotopic incorporation rates to evaluate spatial and temporal changes in caiman isotopic niche width with hierarchical Bayesian models that accounted for habitat use, intraspecific trait variation (sex and body size), and landscape attributes (composition and configuration). We also measured δ13C values of essential amino acids to assess if different primary producers are fueling aquatic food webs in natural and anthropogenic areas. Spatial analysis showed that caiman in agricultural areas had larger isotopic niche widths, which likely reflects some use of terrestrial resources in environments dominated by C4 plants. Patterns in δ13C values among essential amino acids were clearly different between natural and anthropogenic habitats. Overall, our findings suggest that caimans can persist in heterogeneous landscapes fueled by natural and agricultural energy sources of energy, which has implications for effectively managing such landscapes to maximize biodiversity.